The Impact of Value Co-Creation on Customer Satisfaction with Customer Participation as a Mediator - Arif Fakhrudin; Kifni Yudianto; Djaelani Susanto (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This research aims to understand the role of customer participation and value co-creation in enhancing customer satisfaction. The importance of student satisfaction during their academic journey is highlighted through the value creation process in education. This value creation requires participation between students and educators, which encompasses various behaviors, each playing a significant role in shaping customer perceptions regarding the process and outcomes tied to specific service contexts. In particular, information sharing, responsible behavior, and voluntary in-role feedback are found to be especially important in educational services for achieving student satisfaction during their studies in higher education. This study employs a quantitative method using purposive sampling as the sampling technique. The respondents involved in the research are 100 final-year students at STTKD Yogyakarta. The data analysis technique utilized is Smart PLS version 3.3. The results of this study indicate that customer participation, which includes information sharing, responsible behavior, and voluntary in-role feedback, has a positive and significant impact on value co-creation. The study also reveals that value co-creation positively and significantly influences customer satisfaction.